Mental Health During the First Weeks of the COVID-19 Pandemic in the United States - Killgore, William D. S.; Cloonan, Sara A.; Taylor, Emily C.; Dailey, Natalie S. (Frontiers in Psychiatry, 2021)
Background: By March 2020, the World Health Organization declared the COVID-19 crisis as a worldwide pandemic and many local governments instituted stay-at-home orders and closed non-essential businesses. Within the United States, tens of millions of workers lost their jobs and financial security during the first few weeks of the national response to slow the global pandemic. Because of the enormity of the pandemic and its potential impact on mental health, the objective of the present study was to document the prevalence of mental health problems and their association with pandemic-related job loss during the third week of the nationwide shutdown. Methods: Mental health was assessed via online questionnaires among a representative sample of 1,013 U.S. adults on April 9-10, 2020. Rates of clinically significant mental health outcomes were compared between participants who lost their job as a result of COVID-19 restrictions (17.4%) versus those who did not (82.6%). Bivariate multiple logistic regression identified factors that were predictive of, and protective against, mental health problems. Results: The prevalence of clinically significant symptoms was significantly higher than prior population estimates, ranging from 27-32% for depression, 30-46% for anxiety disorders, 15-18% for acute/posttraumatic stress, 25% for insomnia, and 18% for suicidal ideation. Prevalence estimates were 1.5-1.7 times higher for those who reported job loss due to COVID-19 restrictions than those who did not. Mental health problems were predicted by worry over financial instability, insomnia, social isolation, and alcohol consumption, while getting outside more often, perceived social support, and older age were protective. Conclusions: During the first three weeks of lockdowns/stay-at-home restrictions, mental health problems, including depression, anxiety, insomnia, and acute stress reactions were notably elevated relative to prior population estimates. Job loss related to the nationwide shutdown was particularly associated with poorer mental health. These findings provide a baseline of mental health functioning during the first weeks of the national emergency and lockdown orders in response to COVID-19.